PRODUCTION MODEL AND FUNCTIONAL CHARACTERISTICS OF UNITS WITH THE PREFIX “ECO-” IN UZBEK LANGUAGE (Global Conference on Multidisciplinary Research and Innovation, 2026)
This article examines the formation models and functional characteristics of units with the “eco-” prefix in the Uzbek language. It analyzes the role of prefixation in the development of ecological terminology, the semantic load of the “eco-” component, and its usage across different domains. The study also explores the lexical-semantic features of eco-units and their activity in modern ecological discourse.
Keywords: Eco-prefix, ecological terminology, word formation, prefixation, derivation, ecological lexicon, eco-lexemes, functional semantics, ecological discourse.